Nilai Pendidikan Islam Yang Terkandung Dalam Tri Satya Pramuka Tingkat Penggalang (Studi Analisis Buku Boyman Karya Andri Bob Sunardi) - Ahmad Fadholi; Ahmad Saefudin (IAIN Ambon, 2021)
This study aims to describe the content of the values of Islamic education contained in the Scout Promise level of the Boys and Girls Scout in Andri Bob Sunardi's Boyman book and to analyze their implementation in the school environment. This study uses a qualitative approach and the type of research is literature research that focuses on content analysis. Researchers in this case collect and obtain data sourced from library research such as books, literature, and collections owned by libraries as well as scientific works relevant to the research. The results showed that there are values of Islamic education contained in the Scout Promise of the level Boys and Girls Scout and their implementation in the school environment. The values of Islamic education are contained in the obligations of the Scout Promise at the Boys and Girls Scout level which includes 3 things, namely values related to Allah (hablu min Allah), values related to humans (hablu min an-nas), and values related to nature (hablu min al-alam). The implementation of the values of Islamic education contained in the Scout Promise level in the school environment consists of 3 forms of implementation. Namely the implementation of values related to God, the implementation of values related to fellow humans in the school environment, and the implementation of values related to nature in the school environment